Acteurs et enjeux de la néotoponymie des territoires ethniques des grandes métropoles aux Etats-Unis : l’exemple de Miami - Cédric Audebert (L'Espace Politique)
This reflection presents a diatopic approach which conceptualizes place as the result of contradictory forces identifiable at different geographic levels of analysis, from the global to the local scope. Contemporary immigration in the U.S. has profoundly transformed the social and cultural environment of metropolitan areas. In a society where organizational patterns of immigrants and minorities are identifiable in the urban structure, interactions between the immigrant communities and the receiving society translate themselves into an institutionalization of the ethnic neighborhood. In this process of ethnic qualification of urban places, recent toponymic strategies play a major symbolic role. For example, in Miami where 60 % of the population is of Caribbean descent, the renaming of immigrant settlement areas reflects the cultural change of the city and its internationalization as well as its sociospatial segmentation. In parallel, neotoponymy also has a functional dimension in the U.S. society. By the early 1980s, the decision to rename an inner city section of Metropolitan Miami ‘Little Haiti’ came up to the impelling acknowledgement of the Haitian illegal presence by the local and federal authorities. What was at stake was the access to federal resources in order to respond to the tremendous social needs of this marginalized immigrant population. Thus, toponymy appears as an essential tool as well as the result of a power struggle between local power structures (municipalities, county government) and the federal government. At the same time, the stakes are also high at the neighborhood level, where place renaming reveals the changing relations between ethnic communities. One needs to carefully understand the relative significance of toponymy which is indeed often out of step with the more and more complex multiethnicity of U.S. international metropoles.